2018
DOI: 10.1371/journal.pone.0192491
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization mortality and associated risk factors in patients with polymyositis and dermatomyositis: A retrospective case-control study

Abstract: BackgroundPolymyositis and dermatomyositis (PM/DM) are systemic autoimmune diseases with multiple organ involvements that manifest as muscular and cutaneous disorders, interstitial lung disease (ILD) and malignancies. However, information concerning the outcomes and associated factors for PM/DM patients who are hospitalized is limited.MethodsWe retrospectively reviewed the medical charts of PM/DM patients admitted to a Chinese tertiary referral hospital (Peking Union Medical College Hospital, PUMCH) from 2008 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 26 publications
4
28
1
1
Order By: Relevance
“…In the following intragroup analysis, bacterial infection was found to be associated with unfavorable short-term outcome in DM, PM, or CADM patients complicated with AE-ILD. Similar linkage between infection and short-term outcome was seen in IIM patients (3,4). And opportunistic infection was as well-recognized as a major cause of mortality in patients with IIM-related ILD (48).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the following intragroup analysis, bacterial infection was found to be associated with unfavorable short-term outcome in DM, PM, or CADM patients complicated with AE-ILD. Similar linkage between infection and short-term outcome was seen in IIM patients (3,4). And opportunistic infection was as well-recognized as a major cause of mortality in patients with IIM-related ILD (48).…”
Section: Discussionmentioning
confidence: 61%
“…In published studies, the 10-year survival rate for patients with DM, PM, or CADM ranged from 51 to 91% (3). An ∼4.5% in-hospital mortality rate was seen in two retrospective studies (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the serum LDH level has significant correlation with the degree of muscle weakness, muscle destruction, and the degree of muscle inflammation [ 35 ], and that the levels of LDH tend to indicate disease activity [ 27 ]. Serum levels of ESR and CRP are risk factors of interstitial lung disease (ILD) in DM/PM [ 36 39 ], elevated ESR is associated with increased mortality in patients with DM [ 37 , 40 ], and CRP has positive correlation with the global activity scores in DM [ 41 ]. So, to an extent, these parameters can reflect the activity or prognosis of DM/PM.…”
Section: Discussionmentioning
confidence: 99%
“…In the 63 patients of a retrospective Chinese cohort, elevated ESR was an independent risk factor for in-hospital mortality. The patients died of three main causes: infection, ILD, and association of ILD and infection [113]. Go et al [114] reported in a retrospective cohort that DM patients with baseline ESR ≥ 30 mm/h had significantly higher mortality, mainly related to respiratory failure.…”
Section: Resultsmentioning
confidence: 99%